Efforts to Astonish - Gordon, Tom (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2001)
Cocteau always dated his epiphany in the avant-garde to the shock of Stravinsky's revolutionary Le Sacre du Printemps. Diaghilev famously enjoined Cocteau in 1913: "Étonne-moi!" The most tantalizing of Cocteau's efforts to astonish was his proposed 1914 collaboration with Stravinsky, the ballet David, a work previously thought to have left few traces. But even before, Cocteau had embarked on the "molting" which he later credited as his true birth as an artist. Classed by its author as a novel, Le Potomak is part graphic fable, part somnambulant stream-of-consciousness, part compendium of inflammatory aphorisms or, as Cocteau himself declared, a "fever chart"—an aftershock reverie indebted to the composer of Le Sacre. This paper evaluates Le Potomak in the narrative of Cocteau's "astonishment" as an index of the understanding of the musical avant-garde in France during the first decades of the twentieth century.